Optimization of human immunodeficiency virus treatment during incarceration: viral suppression at the prison gate. - Meyer, Jaimie P; Cepeda, Javier; Wu, Johnny; Trestman, Robert L; Altice, Frederick L; Springer, Sandra A (JAMA internal medicine, 2014)
Human immunodeficiency virus (HIV) management in correctional settings is logistically feasible, but HIV-related outcomes before release have not been recently systematically examined.
Keywords: Anti-Retroviral Agents; CD4 Lymphocyte Count; Cohort Studies; Connecticut; Female; HIV Infections; HIV-1; Humans; Male; Prisoners; Prisons; Regression Analysis; Retrospective Studies; Treatment Outcome; Viral Load